Digital fashion heritage: Understanding europeanafashion. eu and the Google Cultural Institute's We Wear Culture. Issue 1 (1st June 2019) - Melchior, Marie Riegels
The digitalization of cultural heritage has become an increasingly common practice among museums and online organizations. Many heritage digitalization projects are driven by an approach called 'sharing is caring'; that is, the purpose of digitalization is accessibility, making what is considered to be valuable cultural heritage an accessible resource for everyone, while stimulating identity production and sympathy for that heritage. The digitalization of fashion heritage can be seen as part of this movement. In recent years, Europeana Fashion (launched in 2015) and the Google Cultural Institute's Google Arts and Culture project, We Wear Culture (launched in 2017), have become major online platforms for the distribution of fashion heritage. The aim of the present article is to explore and understand how fashion heritage is performed by these two online initiatives and what constitutes fashion heritage in this context. The article is based on an explorative analysis of the two digital sites, interviews with the managers of each initiative, as well as insights from existing studies of cultural heritage and digitalization.